Confucius Institutes as Instruments of Soft Power: Comparison with International Rivals - Ngamsang, Sirirat (Journal of Education and Vocational Research, 2013)
The Chinese Confucius Institutes, which have become common around the world and particularly in Asia, have followed the examples of the British Council, Alliance Française and the Goethe Institute. Yet by following the earlier examples, Confucius Institutes have the benefit of late development and can learn from the experiences of earlier approaches. This paper studies and analyses the overseas educations institutions of China, Britain, France and Germany to identify similarities and dissimilarities and then draws conclusions from this. It is shown that Confucius Institutes are a representative of the overseas soft power approach of the Chinese government and have multiple intentions and purposes.